2003
DOI: 10.1093/heapro/18.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Beijing health promoting universities: practice and evaluation

Abstract: The aims of this study were to create a health promoting university within the framework of the Ottawa Charter for Health Promotion. Strategies included reforming and issuing healthy policies, creating a healthy physical and social environment, developing personal health skills, reorienting the health services, and implementing intervention activities. To evaluate the study, 180 students and 120 teaching/administrative staff were sampled for an in-depth interview with open-ended questions administered 1 year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 9 publications
0
47
0
2
Order By: Relevance
“…26 references -relating to the UK, China, Germany, Hong Kong and the USA -conformed to the inclusion criteria. Of these, 15 were authored or co-authored by Dooris or Dooris et al [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and a further seven cited Dooris or Dooris et al [24][25][26][27][28][29][30]. This reflects the relative youth of Healthy Universities as a movement and there was, not surprisingly, a high degree of congruence amongst the papers with regard to the theories and conceptual frameworks deployed.…”
Section: Resultsmentioning
confidence: 99%
“…26 references -relating to the UK, China, Germany, Hong Kong and the USA -conformed to the inclusion criteria. Of these, 15 were authored or co-authored by Dooris or Dooris et al [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and a further seven cited Dooris or Dooris et al [24][25][26][27][28][29][30]. This reflects the relative youth of Healthy Universities as a movement and there was, not surprisingly, a high degree of congruence amongst the papers with regard to the theories and conceptual frameworks deployed.…”
Section: Resultsmentioning
confidence: 99%
“…In sum, the main findings of this study revealed that a high percentage of college students do not exhibit healthy behaviors, and these can be predicted to some extent by social characteristics. Improving and protecting college students' health and developing health-promoting universities is one of the goals of the World Health Organization (Tsouros et al, 1998;Xiangyang et al, 2003). This should also be a goal for states and universities.…”
Section: Discussionmentioning
confidence: 99%
“…The 'Healthy Universities' systemic and holistic approach is commended and should be adopted as widely as possible. Xiangyang et al (2003) report on the development of health promoting universities across Beijing, acknowledging Fig. 23.2 Healthy Universities-A whole system approach.…”
Section: Interventions and Empirical Studiesmentioning
confidence: 99%